The Use of Antibiotics in COVID-19 Therapy in RSUP Dr. Sardjito Yogyakarta - Putri Dina Mahera Laily; Tri Murti Andayani; Ika Puspitasari (Majalah Farmaseutik, 2023)
As a newly emerging disease initially identified at the end of 2019 in Wuhan, China, COVID-19 has various therapeutic options. The current COVID-19 treatment in Indonesia refers to the licensed treatment based on the Emergency Used Authorization from BPOM, which lists many approved antibiotic therapies. However, inappropriate use of antibiotics is known to have an adverse impact of resistance. Therefore, studies on the use of antibiotics in health care facilities, including hospitals, are pivotal, especially in the management of newly emerging disease of COVID-19. This study aims to describe the use of antibiotics as a therapeutic option for COVID-19 treatments in RSUP Dr. Sardjito Yogyakarta. The research used descriptive analytic method by involving patients, who were tested positive for COVID-19 in the period of February to September 2020 in Dr. RSUP Sardjito Yogyakarta, as the research subjects. Data were collected retrospectively using the drug use listed in the medical records. Data were analyzed based on patient characteristics, antibiotic profile, and final prognosis of treatment outcome. This study revealed that the highest cases occurred in men with 69.4%. The productive age group of 21 to 60 years old was known to be the age group with the highest COVID infection (64%). The most widely used antibiotics were azithromycin (56.5%) and levofloxacin (32.9%). The use of antibiotic therapy in COVID-19 patients at RSUP Dr. Sardjito Yogyakarta has proven to be quite effective with a prognostic rate of 76.5% for patients experiencing recovery.